PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR PKN KELAS III SDN 106814 TEMBUNG - Yulia Nesti (Universitas Muhammadiyah Tangerang, 2022)
Abstract: Development of Learning Video Media to Improve Learning Outcomes of Class III PKN SDN 106814 Tembung. This research is a research and development (Reseach and Development). Then the product of this development research is in the form of video learning media. This study uses the ADDIE (Analysis – Design – Development – implement – Evaluate) model (Paidi, 2012) which has been modified into 3D which has been described in Chapter III, namely Analysis, Design, and Development. The media developed was validated by one material expert and one material expert. Validation by media experts was carried out in 2 stages and resulted in a product in the form of video media that was appropriate for third grade SDN students. Validation by media experts was carried out in 2 stages and resulted in a product in the form of video media that was appropriate for third grade SDN students. Thus the learning video media developed was declared suitable for use in learning. Keywords: Video Media, Video Animation, Pkn Learning. Abstrak: Pengembangan Media Video Pembelajaran Untuk Meningkatkan Hasil Belajar PKN Kelas III SDN 106814 Tembung. Penelitian ini merupakan penelitian pengembangan (Reseach and Developmen). Kemudian produk dari penelitian pengembangan ini berupa media pembelajaran video. Penelitian ini menggunakan model ADDIE (Analysis – Design – Development - implement – Evaluate ) ( Paidi, 2012 ) yang telah dimodifikasi menjadi 3D yang telah dijelaskan pada Bab III yaitu Analisis (Analysis), Design (Perancangan), dan Development (Pengembangan). Media yang dikembangkan divalidasi oleh satu orang ahli materi dan satu orang ahli materi. Validasi oleh ahli media dilaksanakan 2 tahap dan menghasilkan produk berupa media video yang layak untuk siswa kelas III SDN . Validasi oleh ahli media dilaksanakan 2 tahap dan menghasilkan produk berupa media video yang layak untuk siswa kelas III SDN. Dengan demikian media video pembelajaran dikembangkan ini dinyatakan layak digunakan dalam pembelajaran.Kata Kunci: Media Video, Video Animasi, Pembelajaran Pkn.